DIGITAL INCLUSION AND TECHNOLOGY: EMPIRICAL RESEARCH ON THE FUNDAMENTAL RIGHT OF ACCESS TO INFORMATION - Barreto Junior, Irineu Francisco (2016)
This article examines one of the main public policies for digital inclusion developed in Brazil, the implementation of Telecentre units, which is one of the initiatives in the e- government plan. Research conducted a case study focused on the analysis of a program unit, located in the city of Vila Velha-ES. The research showed the limits of public policies for digital inclusion, checked in several aspects that would be decisive for the practical success of digital inclusion in Brazil. Deficits in the public policy system have negatively impacted initiatives to ensure the fundamental right of access to information.